Control method for homogenization of tire cord steel structure
By optimizing the composition and cooling control process of cord steel, the soxunite rate and tissue uniformity are improved, and the problems of low strength and fracture caused by uneven structure of cord steel are solved, and the performance of cord steel is significantly improved.
Patent Information
- Application Number
- CN202411610350.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The cord steel has uneven structure, resulting in low strength and prone to fracture.
By optimizing the component composition of cord steel, especially the content of Cu, Cr and Ni elements, the microstructure of cord steel is composed of soxunite and pearlite, and the soxunite rate reaches more than 90%, and through optimization The cooling control process refines the grain size and avoids the generation of harmful tissue.
The structural uniformity and strength of cord steel are significantly improved, and the occurrence of fracture is avoided.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cord steel, and in particular to a control method for homogenizing cord steel structure. Background Art
[0002] In the automotive industry, tires are the only part of a car that comes into contact with the road, and their performance directly affects the car's driving safety and energy efficiency. Radial tires are favored by the market because of their better stability, lower rolling resistance and longer service life.
[0003] As the skeleton material of radial tires, cord steel is the key to improving the overall performance of tires. The production process of cord steel is to draw the wire rods into filaments. The processing process is to undergo a series of deformations such as stretching, torsion, and bending, which places strict requirements on the uniformity of the cord steel structure. The uneven structure of cord steel is specifically manifested in a low troostite rate. The uneven structure directly affects the strength of cord steel, causing the cord steel to be prone to fracture. In view of this, it is of great significance to develop a control method for the uniformity of cord steel structure. Summary of the invention
[0004] The present invention provides a control method for homogenizing the cord steel structure, which solves the problems of uneven cord steel structure and low strength in the related art.
[0005] The technical solution of the present invention is as follows: The present invention provides a control method for homogenizing the structure of a cord steel, comprising the following steps: S1. Pretreatment: After the molten iron is desulfurized, pretreated molten iron is obtained; S2, smelting: adding scrap steel to the pretreated molten iron, smelting, tapping, and obtaining smelted molten steel; S3, refining: adjusting the chemical composition of the smelted molten steel, refining, and soft argon blowing to obtain refined molten steel; S4, continuous casting: the refined molten steel is cast to obtain a continuous casting billet; S5, blanking: the continuous casting blank is heated and blanked to obtain an intermediate blank; S6, rolling: rolling the intermediate billet to obtain a wire rod; S7, spinning: after spinning and cooling, the wire rod is rolled up to obtain cord steel; The cord steel is composed of the following components in weight percentage: C 0.80%~0.85%, Si 0.15%~0.30%, Mn0.45%~0.60%, P≤0.02%, S≤0.015%, Cu 0.012%~0.048%, Cr 0.012%~0.054%, Ni 0.028%~0.048%, Als≤0.003%, Ti≤0.0015%, and the rest is Fe and other inevitable impurities.
[0006] As a further technical solution, the microstructure of the cord steel is troostite and pearlite.
[0007] In the present invention, the microstructure of the cord steel is troostite and pearlite, and does not contain harmful structures such as network ferrite, which avoids the network ferrite from undergoing a large amount of plastic deformation during the drawing process, resulting in a large amount of dislocation accumulation, inducing crack formation and thus causing wire breakage.
[0008] As a further technical solution, the troostite rate of the microstructure is ≥90%.
[0009] In the present invention, the troostite ratio in the microstructure of the cord steel is ≥90%, breaking through the limitation of troostite ratio ≥85% of similar products at home and abroad.
[0010] As a further technical solution, in terms of weight percentage, the relationship among Cu, Cr and Ni satisfies 1≤(Cu+Cr) / Ni≤2.
[0011] In the present invention, when the relationship among Cu, Cr and Ni satisfies 1≤(Cu+Cr) / Ni≤2, it is helpful to further increase the sorbite ratio of the cord steel, and further improve the structural uniformity and strength of the cord steel.
[0012] As a further technical solution, the weight percentage of Cu is equal to the weight percentage of Cr.
[0013] In the present invention, when the relationship among Cu, Cr and Ni satisfies 1≤(Cu+Cr) / Ni≤2 and the weight percentage of Cu is equal to the weight percentage of Cr, it helps to further increase the troostite rate of the cord steel and further improve the structural uniformity and strength of the cord steel.
[0014] As a further technical solution, in step S1, in the pretreated molten iron, S≤0.01% and P≤0.01% by weight.
[0015] In the present invention, by controlling the contents of S and P in the molten iron after pretreatment, the contents of S and P in the final components of the cord steel are effectively ensured to be within an ideal range, thereby avoiding the phenomenon that the cord steel breaks when deep drawing, torsion and subjected to alternating loads due to the cold brittleness and hot brittleness easily caused by S and P.
[0016] As a further technical solution, in step S3, the soft argon blowing treatment is performed for a time of ≥20 min.
[0017] As a further technical solution, in step S5, the heating includes a heating section and a soaking section; During the heating stage, the temperature is 1070-1090°C and the time is 50-70 minutes; During the soaking stage, the temperature is 1090-1110° C. and the time is 50-70 minutes.
[0018] As a further technical solution, in step S6, during the rolling, the starting rolling temperature is 900-930°C, and the final rolling temperature is 1000-1050°C.
[0019] In the present invention, by optimizing the temperature during rolling, it is helpful to refine the original austenite grain size, thereby refining the sorbite grain size.
[0020] As a further technical solution, in step S7, the temperature during spinning is 910-930°C.
[0021] As a further technical solution, in step S7, the cooling includes first stage cooling, second stage cooling and third stage cooling; During the first stage of cooling, the steel is cooled to 800°C at a cooling rate of 22-24°C / s; During the second stage of cooling, the temperature is cooled to 650°C at a cooling rate of 18-20°C / s; During the third stage of cooling, the temperature is cooled to 500° C. at a cooling rate of 5 to 10° C. / s.
[0022] In the present invention, by optimizing the controlled cooling process, especially the controlled cooling process and cooling rate before phase transformation, the troostite rate of the cord steel is further increased, and the organization uniformity and strength of the cord steel are further improved.
[0023] As a further technical solution, in step S7, the temperature during coiling is 400-450°C.
[0024] The working principle and beneficial effects of the present invention are: In the present invention, by optimizing the component composition of the cord steel, especially by optimizing the contents of Cu, Cr and Ni elements, the microstructure of the cord steel is composed of troostite and pearlite, and the troostite rate can reach more than 90%, thereby avoiding the generation of harmful structures such as martensite, network cementite and network ferrite, and significantly improving the organizational uniformity and strength of the cord steel. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1 A control method for homogenizing the steel cord structure comprises the following steps: S1. Pretreatment: After the molten iron is desulfurized, pretreated molten iron is obtained; Among them, in terms of weight percentage, S 0.01% and P 0.01% in the pretreated molten iron; S2, smelting: according to the target composition, Q195 scrap steel is added to the pretreated molten iron, smelting, tapping, and obtaining smelted molten steel; S3, refining: adjusting the chemical composition of the smelted molten steel according to the target composition, refining, and soft argon blowing for 20 minutes to obtain the refined molten steel; S4, continuous casting: the refined molten steel is cast to obtain a continuous casting billet; S5, blanking: After the continuous casting blank is heated and blanked, an intermediate blank is obtained; The heating process includes a heating section and a soaking section. In the heating section, the temperature is 1070°C and the time is 70 minutes. In the soaking section, the temperature is 1090°C and the time is 70 minutes. S6, rolling: the intermediate billet is rolled to obtain a wire rod; During rolling, the starting rolling temperature is 900°C and the final rolling temperature is 1000°C; S7, spinning: the wire rod is spun at 910°C, cooled, and then rolled at 400°C to obtain a cord steel with a diameter of 5.5 mm; The cooling process includes first-stage cooling and second-stage cooling. In the first-stage cooling process, the temperature is cooled to 650°C at a cooling rate of 18°C / s; in the second-stage cooling process, the temperature is cooled to 500°C at a cooling rate of 5°C / s. The cord steel is composed of the following components in weight percentage: C 0.80%, Si 0.15%, Mn 0.45%, P 0.02%, S0.015%, Cu 0.012%, Cr 0.012%, Ni 0.028%, Als 0.003%, Ti 0.0015%, and the rest is Fe and other inevitable impurities; The microstructure of cord steel is troostite and pearlite.
[0027] Example 2 A control method for homogenizing the steel cord structure comprises the following steps: S1. Pretreatment: After the molten iron is desulfurized, pretreated molten iron is obtained; Among them, in terms of weight percentage, S 0.008% and P 0.008% in the pretreated molten iron; S2, smelting: according to the target composition, Q195 scrap steel is added to the pretreated molten iron, smelting, tapping, and obtaining smelted molten steel; S3, refining: adjusting the chemical composition of the smelted molten steel according to the target composition, refining, and soft argon blowing for 25 minutes to obtain the refined molten steel; S4, continuous casting: the refined molten steel is cast to obtain a continuous casting billet; S5, blanking: After the continuous casting blank is heated and blanked, an intermediate blank is obtained; The heating process includes a heating section and a soaking section. In the heating section, the temperature is 1090°C for 50 minutes. In the soaking section, the temperature is 1100°C for 50 minutes. S6, rolling: the intermediate billet is rolled to obtain a wire rod; During rolling, the starting rolling temperature is 930°C and the final rolling temperature is 1050°C; S7, spinning: the wire rod is spun at 930°C, cooled, and then rolled at 450°C to obtain a cord steel with a diameter of 5.5 mm; The cooling process includes first-stage cooling and second-stage cooling. In the first-stage cooling process, the temperature is cooled to 650°C at a cooling rate of 24°C / s; in the second-stage cooling process, the temperature is cooled to 500°C at a cooling rate of 10°C / s. The cord steel is composed of the following components in weight percentage: C 0.85%, Si 0.30%, Mn 0.60%, P 0.015%, S0.01%, Cu 0.048%, Cr 0.054%, Ni 0.048%, Als 0.002%, Ti 0.001%, and the rest is Fe and other inevitable impurities; The microstructure of cord steel is troostite and pearlite.
[0028] Example 3 A control method for homogenizing the steel cord structure comprises the following steps: S1. Pretreatment: After the molten iron is desulfurized, pretreated molten iron is obtained; Among them, in terms of weight percentage, S 0.008% and P 0.008% in the pretreated molten iron; S2, smelting: according to the target composition, Q195 scrap steel is added to the pretreated molten iron, smelting, tapping, and obtaining smelted molten steel; S3, refining: adjusting the chemical composition of the smelted molten steel according to the target composition, refining, and soft argon blowing for 25 minutes to obtain the refined molten steel; S4, continuous casting: the refined molten steel is cast to obtain a continuous casting billet; S5, blanking: After the continuous casting blank is heated and blanked, an intermediate blank is obtained; The heating process includes a heating section and a soaking section. In the heating section, the temperature is 1090°C for 50 minutes. In the soaking section, the temperature is 1100°C for 50 minutes. S6, rolling: the intermediate billet is rolled to obtain a wire rod; During rolling, the starting rolling temperature is 930°C and the final rolling temperature is 1050°C; S7, spinning: the wire rod is spun at 930°C, cooled, and then rolled at 450°C to obtain a cord steel with a diameter of 5.5 mm; The cooling process includes first-stage cooling and second-stage cooling. In the first-stage cooling process, the temperature is cooled to 650°C at a cooling rate of 21°C / s; in the second-stage cooling process, the temperature is cooled to 500°C at a cooling rate of 8°C / s. The cord steel is composed of the following components in weight percentage: C 0.83%, Si 0.22%, Mn 0.5%, P 0.015%, S0.01%, Cu 0.018%, Cr 0.024%, Ni 0.048%, Als 0.002%, Ti 0.001%, and the rest is Fe and other inevitable impurities; The microstructure of cord steel is troostite and pearlite.
[0029] Example 4 The only difference between this embodiment and embodiment 3 is that, in this embodiment, the cord steel is composed of the following components in weight percentage: C 0.83%, Si 0.22%, Mn 0.5%, P 0.015%, S 0.01%, Cu 0.027%, Cr 0.035%, Ni 0.028%, Als 0.002%, Ti 0.001%, and the rest is Fe and other inevitable impurities.
[0030] Example 5 The only difference between this embodiment and Embodiment 3 is that, in this embodiment, the cord steel is composed of the following components in weight percentage: C 0.83%, Si 0.22%, Mn 0.5%, P 0.015%, S 0.01%, Cu 0.02%, Cr 0.025%, Ni 0.045%, Als 0.002%, Ti 0.001%, and the rest is Fe and other inevitable impurities.
[0031] Example 6 The only difference between this embodiment and Embodiment 3 is that, in this embodiment, the cord steel is composed of the following components in weight percentage: C 0.83%, Si 0.22%, Mn 0.5%, P 0.015%, S 0.01%, Cu 0.04%, Cr 0.02%, Ni 0.03%, Als 0.002%, Ti 0.001%, and the rest is Fe and other inevitable impurities.
[0032] Example 7 The only difference between this embodiment and Embodiment 3 is that, in this embodiment, the cord steel is composed of the following components in weight percentage: C 0.83%, Si 0.22%, Mn 0.5%, P 0.015%, S 0.01%, Cu 0.02%, Cr 0.04%, Ni 0.03%, Als 0.002%, Ti 0.001%, and the rest is Fe and other inevitable impurities.
[0033] Example 8 The only difference between this embodiment and Embodiment 3 is that, in this embodiment, the cord steel is composed of the following components in weight percentage: C 0.83%, Si 0.22%, Mn 0.5%, P 0.015%, S 0.01%, Cu 0.03%, Cr 0.03%, Ni 0.03%, Als 0.002%, Ti 0.001%, and the rest is Fe and other inevitable impurities.
[0034] Example 9 The difference between this embodiment and embodiment 8 is that in this embodiment, in step S7, cooling includes first stage cooling, second stage cooling and third stage cooling; In the first stage of cooling, the steel was cooled to 800°C at a cooling rate of 18°C / s; In the second stage of cooling, the temperature was cooled to 650°C at a cooling rate of 24°C / s; In the third stage of cooling, the steel is cooled to 500°C at a cooling rate of 8°C / s.
[0035] Example 10 The difference between this embodiment and embodiment 8 is that in this embodiment, in step S7, cooling includes first stage cooling, second stage cooling and third stage cooling; In the first stage of cooling, the steel was cooled to 800°C at a cooling rate of 24°C / s; In the second stage of cooling, the temperature was cooled to 650°C at a cooling rate of 18°C / s; In the third stage of cooling, the steel is cooled to 500°C at a cooling rate of 8°C / s.
[0036] Embodiment 11 The difference between this embodiment and embodiment 8 is that in this embodiment, in step S7, cooling includes first stage cooling, second stage cooling and third stage cooling; In the first stage of cooling, the steel was cooled to 800°C at a cooling rate of 22°C / s; In the second stage of cooling, the temperature is cooled to 650°C at a cooling rate of 20°C / s; In the third stage of cooling, the steel is cooled to 500°C at a cooling rate of 8°C / s.
[0037] Comparative Example 1 The only difference between this comparative example and Example 1 is that, in this comparative example, the cord steel is composed of the following components in weight percentage: C 0.80%, Si 0.15%, Mn 0.45%, P 0.02%, S 0.015%, Cu 0.024%, Ni 0.028%, Als 0.003%, Ti 0.0015%, and the rest is Fe and other inevitable impurities.
[0038] Comparative Example 2 The only difference between this comparative example and Example 1 is that, in this comparative example, the cord steel is composed of the following components in weight percentage: C 0.80%, Si 0.15%, Mn 0.45%, P 0.02%, S 0.015%, Cr 0.024%, Ni 0.028%, Als 0.003%, Ti 0.0015%, and the rest is Fe and other inevitable impurities.
[0039] Comparative Example 3 The only difference between this comparative example and Example 1 is that, in this comparative example, the cord steel is composed of the following components in weight percentage: C 0.80%, Si 0.15%, Mn 0.45%, P 0.02%, S 0.015%, Cu 0.026%, Cr 0.026%, Als 0.003%, Ti 0.0015%, and the rest is Fe and other inevitable impurities.
[0040] Comparative Example 4 The only difference between this comparative example and Example 1 is that, in this comparative example, the cord steel consists of the following components in weight percentage: C 0.80%, Si 0.15%, Mn 0.45%, P 0.02%, S 0.015%, Ni 0.052%, Als 0.003%, Ti0.0015%, and the rest is Fe and other inevitable impurities.
[0041] The following performance tests were performed on the cord steels in Examples 1 to 11 and Comparative Examples 1 to 4: ① Sorbite rate: refer to YB / T 169-2014 "Metallographic Detection Method for Sorbite Content in High Carbon Steel Wire Rod" and use the metallographic manual detection method to determine the Sorbite rate, and retain one decimal place for the result; ②Tensile strength: refer to GB / T 228.1-2021 "Tensile test of metallic materials Part 1: Room temperature test method" to test the tensile strength, where the test rate is 0.006s -1 .
[0042] The test results are shown in Table 1 below.
[0043] Table 1 Cord steel performance test results
[0044] From the comparison between Example 1 and Comparative Examples 1 to 4, it can be seen that the organizational uniformity and strength of the cord steel can be significantly improved by optimizing the types and contents of Cu, Cr, and Ni.
[0045] Comparison between Examples 3-4 and 5-6 shows that when the relationship between Cu, Cr and Ni satisfies 1≤(Cu+Cr) / Ni≤2, the uniformity and strength of the cord steel can be further improved. Comparison between Examples 6-7 and 8 shows that when the relationship between Cu, Cr and Ni satisfies 1≤(Cu+Cr) / Ni≤2 and the weight percentage of Cu is equal to the weight percentage of Cr, the uniformity and strength of the cord steel can be further improved.
[0046] Comparison between Examples 8-9 and Examples 10-11 shows that the microstructure uniformity and strength of the cord steel are further improved by optimizing the controlled cooling process, especially the controlled cooling process and cooling rate before phase transformation.
[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A control method for homogenizing the steel cord structure, characterized in that: The following steps are involved: S1. Pretreatment: After the molten iron is desulfurized, pretreated molten iron is obtained; S2, smelting: adding scrap steel to the pretreated molten iron, smelting, tapping, and obtaining smelted molten steel; S3, refining: adjusting the chemical composition of the smelted molten steel, refining, and soft argon blowing to obtain refined molten steel; S4, continuous casting: the refined molten steel is cast to obtain a continuous casting billet; S5, blanking: the continuous casting blank is heated and blanked to obtain an intermediate blank; S6, rolling: rolling the intermediate billet to obtain a wire rod; S7, spinning: after spinning and cooling, the wire rod is rolled up to obtain cord steel; The cord steel is composed of the following components in weight percentage: C 0.80%~0.85%, Si 0.15%~0.30%, Mn0.45%~0.60%, P≤0.02%, S≤0.015%, Cu 0.012%~0.048%, Cr 0.012%~0.054%, Ni 0.028%~0.048%, Als≤0.003%, Ti≤0.0015%, and the rest is Fe and other inevitable impurities.
2. A control method for homogenizing the cord steel structure according to claim 1, characterized in that: In terms of weight percentage, the relationship among Cu, Cr and Ni satisfies 1≤(Cu+Cr) / Ni≤2.
3. A method for controlling the homogenization of cord steel structure according to claim 2, characterized in that: The weight percentage of the Cu is equal to the weight percentage of the Cr.
4. A control method for homogenizing cord steel structure according to claim 1, characterized in that: In step S1, in the pretreated molten iron, S≤0.01% and P≤0.01% by weight.
5. The method for controlling the homogenization of the cord steel structure according to claim 1, characterized in that: In step S3, the soft argon blowing treatment lasts for ≥ 20 min.
6. A control method for homogenizing cord steel structure according to claim 1, characterized in that: In step S5, the heating includes a heating section and a soaking section; During the heating stage, the temperature is 1070-1090°C and the time is 50-70 minutes; During the soaking stage, the temperature is 1090-1110° C. and the time is 50-70 minutes.
7. A method for controlling cord steel structure homogenization according to claim 1, characterized in that: In step S6, during the rolling, the starting rolling temperature is 900-930°C, and the finishing rolling temperature is 1000-1050°C.
8. The method for controlling the homogenization of cord steel structure according to claim 1, characterized in that: In step S7, the temperature during spinning is 910-930°C.
9. A method for controlling cord steel structure homogenization according to claim 1, characterized in that: In step S7, the cooling includes first stage cooling, second stage cooling and third stage cooling; During the first stage of cooling, the steel is cooled to 800°C at a cooling rate of 22-24°C / s; During the second stage of cooling, the temperature is cooled to 650°C at a cooling rate of 18-20°C / s; During the third stage of cooling, the temperature is cooled to 500° C. at a cooling rate of 5 to 10° C. / s.
10. The method for controlling the homogenization of cord steel structure according to claim 1, characterized in that: In step S7, the temperature during coiling is 400-450°C.
Citation Information
Patent Citations
Boron-containing high-end cord steel and production method thereof
CN105063508A
Steel wire rod for superfine steel cord subjected to heat reduction treatment and production process of steel wire rod
CN114686780A
Ultrahigh-strength 85-grade tire cord steel wire rod and production method thereof
CN115976415A
Molding control method for cord steel inclusions
CN116814890A
Ultra-high-strength 90-grade tire cord steel wire rod and production method thereof
CN118563068A